2020
DOI: 10.1111/jam.14916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air, water and dock microbial communities on boat microbial community composition

Abstract: Aims: This study explores the microbial diversity of sources which may influence boat microbial communities. We investigated the impact of dock, air and water microbial communities on the hull, transom and bilge microbial communities over the span of 11 days. Methods and Results: Using source tracking software, we investigated the extent to which each of our potential sources (air, water and dock) influenced the overall microbial community. This study concluded that the dock impacted 14-64% of the hull and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Therefore, microbes from terrestrial environments could be seeding coastal surfaces through dust deposition following aerosolization [53]. Although a diverse population of microbes are present in ambient air, a recent short-term temporal study revealed that airborne bacteria only contributed minimally to the external surfaces of boats docked in the port [54], suggesting that airborne sources may not be a major source of microbiomes in the open pier environment.…”
Section: Microbial Sources That Shape the Pier Surface Microbiomesmentioning
confidence: 99%
“…Therefore, microbes from terrestrial environments could be seeding coastal surfaces through dust deposition following aerosolization [53]. Although a diverse population of microbes are present in ambient air, a recent short-term temporal study revealed that airborne bacteria only contributed minimally to the external surfaces of boats docked in the port [54], suggesting that airborne sources may not be a major source of microbiomes in the open pier environment.…”
Section: Microbial Sources That Shape the Pier Surface Microbiomesmentioning
confidence: 99%